A molecular epidemiological study of the hepatitis B virus in Thailand after 22 years of universal immunization. Issue 4 (8th September 2015) - Yimnoi, Parichat; Posuwan, Nawarat; Wanlapakorn, Nasamon; Tangkijvanich, Pisit; Theamboonlers, Apiradee; Vongpunsawad, Sompong; Poovorawan, Yong
Abstract : Hepatitis B virus (HBV) infection affects an estimated two billion people worldwide. Since 1992, Thailand implemented universal HBV vaccination as part of the expanded program on immunization (EPI) for newborns. This study aims to compare genotypes and characterize HBV by assessing pre‐S / S and basic core promoter (BCP)/precore (PC) mutations in populations born before and after EPI implementation. A nationwide serosurvey conducted in 2014 assessed the impact of universal HBV vaccination in Thailand. Two cohort groups were established based on whether they were born before or after 1992. HBV DNA was amplified from HBsAg positive samples by PCR and sequenced. HBV genotypes, pre‐S/S regions, and BCP/PC mutations were characterized. From a total of 5, 964 subjects, there were 2, 805 (47.0%) and 3, 159 (53.0%) individuals who were born before and after EPI implementation, respectively. The overall prevalence of HBsAg was 2.2%. The prevalence of HBsAg was significantly higher in the before EPI group (4.3%) than in the after EPI group (0.3%) ( P < 0.001). HBV DNA was detected in 119 samples; 111 HBV‐positive samples (93%) were genotype C (subgenotype C1). The "a" determinant mutation was only detected in the "before EPI" group. Twenty‐two years after implementation of the EPI program, the HBV carrier rate is significantly reduced. The most prevalent genotype for the remaining HBV was C1. The "vaccine escape" mutant, especially the "a" determinant, was not detected after the launch of the EPI program, and the current HBV vaccine remains highly effective. J. Med. Virol. 88:664–673, 2016 . © 2015 Wiley Periodicals, Inc.